Audit Sistem Pencahayaan pada Gedung Sekolah B Politeknik Negeri Semarang - Pangestuningtyas Diah Larasati; Adeguna Ridlo Pramurti; Adi Wasono; Lilik Eko Nuryanto; Septiantar Tebe Nursaputro; Muhammad Bhayu Bramantyo (STEKOM PRESS, 2026)
School Building B of Politeknik Negeri Semarang (POLINES) is an intensively used academic facility that requires a comprehensive evaluation of its lighting energy consumption. A lighting system energy audit was conducted using a quantitative descriptive method through direct measurements with a lux meter and laser meter. The results indicate that only 6 out of 41 rooms met the minimum illuminance standard of SNI 6197:2020, while 5 rooms exceeded the maximum LPD limit of 7.53 W/m², primarily due to the use of inappropriate lamp types and sizes relative to room dimensions, as well as performance degradation from aging lamps. Replacing conventional lamps with LED technology and adjusting the number of luminaires based on illuminance requirement calculations are recommended as corrective measures, which are proven to reduce LPD values below the maximum standard limit while improving visual comfort for building occupants.